KAJIAN KOMPARATIF PERUBAHAN SOSIAL DALAM PERSPEKTIF KARL MARX DAN EMILE DURKHEIM - Abdillah, Ligar; Triyanto, Triyanto; Sopar, Sopar (Universitas Teuku Umar, 2024)
Social change is an essential part of societal dynamics and a significant focus in the evolution of social sciences, which examine various aspects such as values, norms, and social structures. This study aims to illustrate the differing paradigms of classical sociological figures, namely Karl Marx and Emile Durkheim, in analyzing social change within society. The research employs a descriptive qualitative approach and literature review in its data collection process. The analysis in this study not only outlines the contrasting perspectives of these two thinkers but also describes the relevance of their ideas to contemporary phenomena of social change. The findings reveal fundamental differences: Karl Marx firmly relies on the concept of historical materialism to critically examine social change, emphasizing economic conditions as a driving factor. In contrast, Emile Durkheim explains that social change is not rooted in conflict and opposition but rather a process of societal adaptation to maintain social order and preserve social solidarity. This study underscores the need to explore more contemporary forms of social change, such as extreme climate shifts, digitalization, and social movements, to make classical theories more applicable to current realities.